The Impact of Interactive Digital Storytelling Apps on English Vocabulary Acquisition for Young English Learners in South Kalimantan, Indonesia - Lailatul Kodriyah; Neneng Islamiah; Hengki Hengki (Intensive Journal, 2025)
This study investigates the impact of interactive digital storytelling apps on vocabulary acquisition among young English learners in Indonesia. A quasi-experimental design was employed, involving 60 students aged 8-10 years, divided into an experimental group using digital storytelling apps and a control group using traditional storytelling methods. Over a 6-week intervention period, both groups were assessed using pre- and post-tests to measure their vocabulary acquisition. The results demonstrated that the experimental group showed a significant improvement in vocabulary acquisition, with a 30% increase in post-test scores compared to a 15% increase in the control group. T-test analysis confirmed the statistical significance of the differences in vocabulary acquisition between the groups (p < 0.001). The findings suggest that interactive digital storytelling is effective for enhancing vocabulary acquisition and engagement in young English learners. The study underscores the potential benefits of integrating technology into early language education while addressing practical challenges such as teacher training and access to resources. Future research should explore the long-term impacts and broader applications of digital storytelling in language learning.